Migration, Agglomeration and Attractiveness of Cities in China - Luo Xubei; Nong Zhu (Fondation pour les études et recherches sur le développement international (FERDI), 2022)
This study aims to identify drivers of spatial migration in the context of regional structural transformation towards clean and connected cities. Using two surveys of floating population covering all cities, conducted by China Family Planning Commission in 2010 and 2014, we examine the effect of city characteristics and local policies on the mobility of migrants. Our analyses show that city size, wage level, sectoral composition, ownership structure of enterprises, and healthcare service provision are important factors that condition migratory inflow; their effect varies across migrants with different characteristics. While most of migrants moved to the regional hubs, migration to cities other than hubs has increased in the 2010s and many medium and small cities have become more attractive.
Keywords: 330